Language Functions of the Main Character in Spiderman: No Way Home Movie Script - Robert Kristian Adinata; I Gusti Ayu Vina Widiadnya Putri (ELYSIAN JOURNAL : English Literature, Linguistics and Translation Studies, 2025)
This study focuses on the language function used by the main character in the movie "Spiderman: No Way Home". The aim is to trace the use of language functions and describe the dominant types of language functions used in the film "Spiderman: No Way Home". The data is the dialogue of the main characters in the movie "Spiderman: No Way Home". This research was conducted using descriptive qualitative research. The findings show that there are six types of language functions used by the main character in the movie "Spiderman: No Way Home". They are expressive, directive, referential, metalinguistic, phatic, and poetic. The most dominant type of language function is metalinguistics. This study aims to determine the grammar used in the film "Spiderman: No Way Home". This film is intended for all ages because it is a family film and it can be seen by children. The theory used is anchovy from Halliday (1978). The study found the context of the function of the message conveyed and the pronunciation of the main character in the movie "Spiderman: No Way Home". It can then be revealed how language works and how to pronounce it.